Negative associations of age and lifestyle factors with the antibody response to the COVID-19 vaccine BNT162b2 in health workers from Spain - Sarabia de Ardanaz, Luis; Serrano-Conde, Esther; Fuentes, Ana; Leyva, Alba; García, Federico; Requena, Pilar (Frontiers in Immunology, 2025)
IntroductionDespite the high efficacy of the anti-coronavirus disease 2019 (COVID-19) BNT162b2 vaccine (Comirnaty®, Pfizer-BioNTech), variability in the antibody titers following vaccination has been described. However, little is known about the risk factors that are associated with a poorer antibody response to the BNT162b2 vaccine.MethodologyWe studied the determinants of the humoral response to the anti-COVID-19 vaccine BNT162b2 in 200 healthcare workers followed up for 2 years. Serum samples were tested for the anti-spike immunoglobulin G (IgG) levels and neutralizing antibody titers against selected severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants at different time points after primary and booster vaccinations. Anthropometric data and clinical and lifestyle information were also collected. Statistical analyses consisted of linear and logistical regressions for point estimations and the Mann–Whitney, Friedman, and generalized estimating equations for repeated measures.ResultsAfter the primary vaccination, the antibody titers and the percentage of seroconverted individuals peaked at 5 weeks but declined after 1 year; however, they remained high after the booster administration. After the first dose of the vaccine, negative associations of the anti-spike IgG levels with age (β = −0.01, 95%CI = −0.03 to −0.003), smoking habit (β = −1.08, 95%CI = −1.70 to −0.46), and alcohol consumption (β = −1.43, 95%CI = −2.20 to −0.65) were found. With regard to the booster vaccine, the following associations were retained in the stepwise multivariate model: anti-Delta neutralizing antibodies with hip circumference (OR = 1.07, 95%CI = 1.01–1.12, p = 0.008), anti-Delta-K antibodies with hip circumference (OR = 1.06, 95%CI = 1.01–1.11, p = 0.007), and anti-Omicron antibodies with the Mediterranean diet score (OR = 0.74, 95%CI = 0.58–0.96, p = 0.023).ConclusionLifestyle habits and age had an association with the humoral response to the BNT162b2 vaccine.